2002
DOI: 10.1210/jc.2002-020855
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Picture of Celiac Disease in Turner Syndrome

Abstract: A multicenter study of Turner syndrome (TS) patients was carried out to estimate the prevalence of celiac disease (CD) and to detect clinical characteristics and laboratory data of affected patients. Three hundred eighty-nine girls with TS were screened by IgA antigliadin antibodies and/or antiendomysial antibodies. Intestinal biopsy was offered to positive cases. CD was diagnosed in 25 patients. In celiac subjects, anemia, anorexia, and delayed growth (with respect to Italian TS curves) were frequently presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
2
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(95 citation statements)
references
References 36 publications
5
81
2
7
Order By: Relevance
“…A higher prevalence of CD is found also among girls with Turner's syndrome 28 and children with Down's syndrome. 29 …”
Section: Box 1 Difficulties In Complex Inheritancementioning
confidence: 92%
“…A higher prevalence of CD is found also among girls with Turner's syndrome 28 and children with Down's syndrome. 29 …”
Section: Box 1 Difficulties In Complex Inheritancementioning
confidence: 92%
“…Given the background prevalence of celiac disease of 1:100, there are populations that are at an increased risk for disease, including patients with type 1 diabetes (26), autoimmune thyroid disease (both hyper-and hypothyroidism) (27,28), relatives of patients with celiac disease (3) and type 1 diabetes and patients with Turner (29,30) and Down syndromes (31). Rates of celiac disease in these populations range from 5-10%.…”
Section: Epidemiology (Table 2)mentioning
confidence: 99%
“…Celiac disease related antibodies have been identified in between 4-6% of girls with Turner Syndrome, the diagnosis of celiac disease can be made as early as 4 years of age (30,29). Recently published clinical practice guidelines for the care of girls with Turner syndrome recommend screening for celiac disease beginning at age 4 with measurement of TG autoantibodies.…”
Section: Associated Conditions (Table 1)mentioning
confidence: 99%
“…It has long been recognized that there is an increased incidence of autoimmune disorders in TS (1), with hypothyroidism being the most common. Many studies have reported an increased prevalence of coeliac disease (CD) in TS (2)(3)(4)(5)(6)(7)(8)(9), with prevalences reported of 0-8.1%, compared with 0.5-1.0% in the general population, based on serological screening (10).…”
Section: Introductionmentioning
confidence: 99%